A drain-current model for DG PMOSFETs with fabricated 35 nm device comparison. (15th March 2007) - Mckenzie, Todd G.; Li, Yiming
This work presents a continuous, analytic drain-current model for symmetric DG PMOSFETs. The model is derived from the closed form solution of Poisson's equation and current continuity equation without the charge sheet approximation. The model is extended to include the mobility degradation effect. In addition, a fast solver is presented which determines drain current to within a user-defined accuracy. The new model is fit to hardware, and I–V curves comparing the analytic model to experimental data are shown.